Line-of-sight effects on strong lensing time delays - Johnson, Daniel (Department of Astronomy, 2024)
The effects of matter along the line-of-sight in strong gravitational lensing systems is widely recognised to have a non-negligible effect on lensing observables. In this project, we explore the Dominant-Lens Approximation, a new theoretical formalism designed to parameterise these effects, paying particular attention to degeneracies between line-of-sight effects and the properties of the main lens, and the influence of these effects on measurements of strong lensing time delays. We implement this formalism in the tidal regime as a new sub-package in the open-source lens modelling software package lenstronomy. Using this implementation, we generate mock lens images and measured time delay data, and investigate the prospects of measuring properties of the line-of-sight from these data. We also explore the consequences of under-parameterised line-of-sight effects on measurements of the Hubble constant from time delay cosmography. We find that images of lensed extended sources are those from which precise measurements of line-of-sight shears are most likely to be obtained, but that lensed point source images and time delay data can serve as valuable constraints on noisier images. For measurements of both the shear and the Hubble constant, under-parameterised lens models which exclude the foreground shear term lead to significant biases.